Protective Effects of a Probiotic Lacticaseibacillus paracasei MSMC39-1 on Kidney Damage in Aged Mice: Functional Foods Potential - Pol Sookpotarom; Jirapat Namkaew; Kaikwa Wuttisa; Chantanapa Chantarangkul; Praewpannarai Jamjuree; Thiranut Jaroonwitchawan; Malai Taweechotipatr (Foods)
Kidney fibrosis and inflammation are significant contributors to the decline in renal function associated with aging. These processes are characterized by structural changes, such as glomerular sclerosis and interstitial fibrosis, which exacerbate kidney injury and inflammation in aged individuals. Probiotics have gained increasing attention for their potential health-promoting effects. However, further investigation is required to fully understand the mechanisms underlying these benefits. We hypothesize that probiotics could ameliorate fibrosis through the immunomodulatory effects of probiotics and by improving kidney tissue inflammation. Sixteen-month-old aging mice were administered Lacticaseibacillus paracasei MSMC39-1 for four months compared to young mice (six-month-old) and aged mice (twenty-month-old). The research found that following the administration of probiotic MSMC39-1, there were significant improvements in kidney inflammation, as evidenced by reductions in pro-inflammatory cytokines, fibrosis, and inflammatory cells within the tissue. Moreover, the findings demonstrated that probiotic MSMC39-1 significantly normalized levels of malondialdehyde (MDA), and rescued antioxidant superoxide dismutase (SOD) and glutathione peroxidase (Gpx) in kidney tissue which was consistent with a low mitochondria biogenesis. Further investigations revealed that conditioned medium from MSMC39-1 rescued epithelial kidney cells with damage induced by high glucose. This research provides information and insights into the mechanisms underlying the beneficial health effects of probiotics, offering a deeper understanding of how these probiotics contribute to anti-aging processes in the kidney.